Psychoanalysis and Neuroscience: The Bridge Between Mind and Brain - Cieri, Filippo; Esposito, Roberto (Frontiers in Psychology, 2019)
In 1895 in the Project for a Scientific Psychology Freud tried to integrate psychology and neurology in order to develop a neuroscientific psychology. Since 1880 Freud made no distinction between psychology and physiology. His papers from the end of the 1880s to1890 were very clear on this scientific overlap: as with many of its contemporaries, Freud thought about psychology essentially as the physiology of the brain. Years later he had to surrender, realizing a technological delay, not capable to pursue its ambitious aim, and until that moment psychoanalysis would have to use its more suitable clinical method. Also, he seemed skeptical about the phrenology drift, typical of that time, in which any psychological function needed to be located in its neuroanatomical area. He could not see the progresses of neurosciences and its fruitful dialogue with psychoanalysis, occurred also thanks to the improvements in the field of neuroimaging, which has made possible a remarkable advance in the knowledge of the mind-brain system and a better observation of the psychoanalytical theories. After years of investigations, deriving from research and clinical work of the last century, the discovery of neural networks, together with the free energy principle, we are observing under a new light the psychodynamic neuroscience in its exploration of the mind-brain system. In this narrative review we summarize the important developments of the psychodynamic neuroscience, with particular regard to the free energy principle, the resting state networks, especially the Default Mode Network in its link with the Self; finally we suggest a discussion by approaching the concept of Alpha Function, proposed by the psychoanalyst Wilfred Ruprecht Bion, trying to speculate about the connection with neuroscience.